Emergency Prevention, Preparedness and Response (EPPR) Work Plan - Emergency Prevention, Preparedness and Response (EPPR) (Arctic Council Secretariat, 2017)
EPPR will develop project proposals within this mandate for approval as Arctic Council projects, taking into account the needs of indigenous peoples and incorporating traditional and local knowledge when appropriate. The projects identified in this work plan include projects that have already been approved by EPPR and projects that are under development for future EPPR review and approval. Additional project proposals may be developed within the scope of this work plan between 2017-2019. Implementation of projects is subject to secure financing.